NAFAS: Non-Rigid Air Flow Active Sensor, a Cost-Effective, Wearable, and Ubiquitous Respiratory Bio-Sensor - Annabestani, Mohsen; Esmaeili-Dokht, Pouria; Nejad, Sina Khazaee; Fardmanesh, Mehdi (IEEE sensors journal, 2021)
A Non-rigid Air Flow Active Sensor (NAFAS) to detect the respiratory patterns is introduced in this paper. The main part of NAFAS is an ionic electroactive polymer-based ( {i} -EAP) soft sensor. It can accurately detect breathing patterns and has promising features to develop low cost, wearable, and ubiquitous spirometers. Patients with respiratory diseases need to take pulmonary function tests consistently. Hence, it is time-consuming and expensive. To address these problems, NAFAS presents point-of-care testing (POCT) of the respiratory system's function. The proposed {i} -EAP based sensor is a small strip of Ionic Polymer Metal Composite (IPMC) that has been fabricated using a Nafion membrane and two Pt electrodes. A test, including different breathing patterns, is designed and is performed by several male and female subjects. Results show that the NAFAS can detect delicate breathing patterns with various frequencies in an appropriate manner.